Модель механізму інтегрування складових систем менеджменту підприємств на засадах інтелектуалізації управління - Ситник, Й. С. (Видавництво Львівської політехніки, 2017)
Досліджено сутність та виокремлено рівні інтегрування складових систем менедж- менту підприємств на засадах інтелектуалізації управління. Сформовано цільові та пред- метні різновиди інтеграції підсистем менеджменту у процесі інтелектуалізації. Визначено, що метою інтегрування є досягнення власних або спільних цілей, створення власних або спільних продуктів підсистем із високим рівнем їх синергійності та емерджентності. З’ясовано, що рівень активації інтелектуально-знаннєвих активів у системі менеджменту підприємств залежить від світоглядного, організаційного, мотиваційного, культурологіч- ного аспектів, які культивуються у середовищі систем та окремими інтелектоносіями. Сформовано модель інтегрування підсистем та інтелектоносіїв у системі менеджменту підприємств у процесі їх взаємодії. Розроблено організаційно-функціональну модель механізму інтегрування підсистем (інтелектоносіїв) у системі менеджменту на засадах інтелектуалізації, яка передбачає поетапне здійснення шести основних функцій.

In the article investigational essence and even integrations of the component systems of management of enterprises are selected on principles of intellectualization of management. It is made to order to consider the basic levels of integration in the systems of management of enterprises: between subsystem, internal subsystem, functional, professionally intellectual, personality subsystem, personality system, system (subsystem) - external, personality external. The having a special purpose and subject varieties of integration of management subsystems are formed in the process of intellectualization. Their essence is that in the structure of the management system there is a row of management (media intelligence) subsystems which carry out the processes of integration in relation to a trade-out intellectual-knowledge assets. The purpose of integration is achievement of own or general aims, creation of own or general products of subsystems with a high level them synergistic and emergent. Intellectualknowledge assets of the systems of management of enterprises unlike material, financial, investment, labour, actually simultaneously and in full can be activated in space and time. In different projects, subsystems and systems of management of internal and external environments. Level of activating intellectual-knowledge assets in the system of management of enterprises depends on a world view, organizational, motivational, cultural aspects which Lviv Polytechnic are cultivated in the environment of the systems and separate media intelligence. The model of integration of subsystems and media intelligence is formed in the system of management of enterprises in the process of their co-operation. It is suggested the basic forms of integration to consider: advising, exchange intellectual-knowledge assets, intelligence policies, impresario, coordination, experimental centres, management intellectual-knowledge assets, forming of ownership rights on intellectual-knowledge assets. By basic integrative strategies certainly integration is a “sentinel”, integration is “spatial” and integration is “administrative”. The condition of forming of effective case of enterprises frame on principles of integration and intellectualization is an active exchange by intellectual-knowledge products between subsystems (media intelligence), which must be formalized in part of authentication, control and fixing of intellectual ownership rights. The organizationally functional model of mechanism of integration of subsystems (media intelligence) is developed in the system of management on principles of intellectualization which foresees stage-by-stage realization of six basic functions. Monitoring of process of intellectualization and integration in the systems of management of enterprises. Evaluation of process of intellectualization of the systems of management and his effectiveness. Determination of factors of actualization of processes of integration on principles of intellectualization. A lineation of the stages of realization of processes of integration of subsystems (media intelligence) is in the system of management. Development of strategy, tactic and form of integration of subsystems (media intelligence) is in the system of management. Providing of realization of initiatives is from integration of subsystems (media intelligence) in the system of management..
A model of mechanism of integration of the component systems of management of enterprises is on the basis of intellectualization of management
Keywords: інтеграція; підсистема; інтелектоносій; система менеджменту; інтелектуалізація; модель; механізм; критерій; integration; subsystem; media intelligence; management system; intellectualization; model; mechanism; criterion; 005.336.4; 334.716